PASAR MATA UANG ASING - Kunarjo, Santi (Manajemen Bisnis Kompetensi, 2008)
The exchange rate is the price of a national currency expressed in terms of a foreign currency. The notion of an exchange rate refers to the broader notion of convertibility. A currency is said to be convertibled if it can be legally exchanged and accepted for another currency. Meanwhile, foreign exchange is all claimed to foreign currencies and payable abroad, whether consisting of funds held (in foreign currencies) with banks abroad, or bills or cheques, which are also in foreign currencies and payable abroad. In depth, the Foreign Exchange Market is the bridge between two distinct money markets.Ã‚Â Keywords: exchange rate, convertibility, foreign exchange, currencies, market